2014
DOI: 10.1002/lary.24987
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of serial dilation for high‐grade radiation‐related esophageal strictures in head and neck cancer patients

Abstract: Objective Dysphagia and esophageal stricture are frequent consequences of treatment for head and neck cancer. This study examines the effectiveness of the anterograde-retrograde rendezvous procedure and serial dilations in re-establishing esophageal patency to allow return to oral diet and gastrostomy tube removal in a cohort of patients with complete or near-complete esophageal stricture following non-surgical cancer treatment. Study Design Retrospective review of patients treated with radiation therapy wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…BD is a common procedure used to treat CPD and pharyngo-upper esophageal strictures in dysphagia patients [2,6,10,14,15]. There have not been any studies investigated the effectiveness of BD in dysphagia management from the perspective of swallow physiology changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BD is a common procedure used to treat CPD and pharyngo-upper esophageal strictures in dysphagia patients [2,6,10,14,15]. There have not been any studies investigated the effectiveness of BD in dysphagia management from the perspective of swallow physiology changes.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions can be seen in strokes of various locations, including subcortical and supratentorial, lateral medullary and cerebellum [4][5][6]. PSR was also found in head and neck cancer patients [7], most commonly caused by reduced tongue mass and limited tongue mobility that was associated with total or partial glossectomy with or without reconstruction [8,9], and radiation-induced esophageal strictures as well [10]. Radiation therapy post nasopharyngeal carcinoma is associated with impaired pharyngeal contraction, which can lead to PSR [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most authors defined clinical success as resolution of dysphagia (or tolerance of soft diet) measured by different scores [2, 12, 14-16, 18, 19], often requiring a variable dilation-free period [11,13,18,20,21] and considering percutaneous endoscopic gastrostomy (PEG) status [20,22,23]. Francis et al [22] also reported patient satisfaction with the dilation program.…”
Section: Introductionmentioning
confidence: 99%